Luteolin attenuates inflammation and apoptosis in LPS-induced ALI mice by activating the HGF/c-Met pathway - Jihong Bi; Yan Li; Lin Lu; Tingting Yin; Shaohua Mao; Run Zhang; Juan He; Xing Ni; Kai Wang; Jirui Bi (Frontiers in Pharmacology)
ObjectiveTo investigate the protective effects of luteolin on ALI induced by lipopolysaccharide (LPS) in male mice and to explore the underlying mechanisms.MethodsA two-sample Mendelian randomization (MR) analysis was conducted to assess the causal relationship between hepatocyte growth factor (HGF) and acute respiratory distress syndrome (ARDS). Network pharmacology analysis was employed to identify herbs that mitigate inflammation and apoptosis by upregulating HGF expression and to determine the hub active ingredients. These findings were subsequently validated through in vivo experiments using an LPS-induced ALI mouse model. Lung histopathological examination, enzyme-linked immunosorbent assay, and Western blot analysis were performed to evaluate relevant biomarkers of inflammation and apoptosis.ResultsThe MR analysis demonstrated a causal effect of HGF on ARDS (IVW: β = −1.120, OR = 0.326, 95% CI = 0.116–0.916, P = 0.033). Among herbs associated with upregulating HGF expression, Salvia miltiorrhiza Bunge is involved in the negative regulation of apoptotic process and positive regulation of cell population proliferation. Luteolin was identified as the hub active ingredient extracted from S. miltiorrhiza Bunge. In LPS-induced ALI mice, luteolin significantly alleviated histopatholocial damage, inflammation, and apoptosis in the lungs. However, these protective effects were abrogated by c-Met inhibition.ConclusionLuteolin attenuates inflammation and apoptosis in the lungs of LPS-induced ALI mice via activation of the HGF/c-Met pathway.